Identification of the Key Characteristics of Daughter-Father Avoidant Attachment - Nikolić, Marija; Krstić, Ksenija (Psihološka istraživanja, 2023)
The  paper  deals  with  the  daughter-father  avoidant  attachment.  The  purpose  of the  study  is  to  identify  the  characteristics,  relationships  and  behaviour  of  fathers that  are  perceived  by  the  daughters  as  the  key  ones  for  the  formation  of  avoidant attachment  with  fathers.  Bearing  this  in  mind,  the  study  focuses  on  youth  who have  a  combination  of  two  patterns,  secure  attachment  to  the  mother  and  avoidant attachment to the father. The research was designed as a mixed-method study. In the first  phase,  233  young  people  aged  15  to  35  (73.1%  women)  were  included  and  the Experience in Close Relationships Scale was administered. From this sample, we then selected the participants (N=49, 73.6% women, Mage=20.9) who had a combination of secure attachment to the mother and avoidant attachment to the father. The final sample  in  the  second,  qualitative  phase  of  the  research  consisted  of  nine  girls  who accepted  to  be  interviewed.  The  data  were  collected  through  a  semi-structured interview based on the AAI and analysed through Interpretative Phenomenological Analysis.  The  results  point  to  three  identified  topics  common  to  experiences  of  all nine participants. The topics relate to the consequences of fathers’ physical absence during  the  period  of  growing  up  of  their  daughters,  the  consequences  of  the  lack of  two-way  communication  within  the  father-daughter  interaction,  as  well  as  to the  daughters’  feeling  that  the  father  is  a  person  in  whose  presence  they  cannot  act freely and naturally in the way they can act in the presence of the mother, to whomthey are securely attached.
Keywords: Attachment; Avoidant Attachment; Fathers; Daughters; Qualitative Analysis